Health impact studies of climate change adaptation and mitigation measures – A scoping review - Luyten, Axel; Winkler, Mirko S.; Ammann, Priska; Dietler, Dominik (The Journal of Climate Change and Health, 2023)
Climate change affects both mental and physical health. Besides limiting the extent and consequences of climate change, mitigation and adaptation measures can have additional and potentially unintended health impacts. This scoping review outlines how health effects of climate mitigation and adaptation measures have been studied in the scientific literature. We conducted a systematic literature search in the databases PubMed, Scopus and Web of Science without time restriction. All peer-reviewed articles reporting quantified health impacts linked to specific climate change adaptation and mitigation measures were included. Overall, the 89 included articles considered only a narrow range of health determinants and health outcomes. Adaptation- and mitigation-related articles most frequently investigated the environmental health determinants air temperature and air pollution, respectively. Non-communicable diseases were predominantly studied while other relevant health outcome categories, such as mental health, food- and nutrition-related issues, and communicable diseases were rarely reported. The scarcity of studies focusing on the social health determinants and providing stratified health impacts among vulnerable population groups in assessments points to an inadequate consideration of health equity aspects. Increased efforts to quantify health impacts more comprehensively and to identify underlying vulnerability factors among specific population groups seem needed. This information could provide policymakers with more accurate evidence to address health equity aspects, limit adverse health impacts and promote health co-benefits of climate change adaptation and mitigation measures.
Keywords: openalex:citedBy; openalex:import; selected_for:effects of climate ch...on learning...LMICs 2024; tagged